2021
DOI: 10.2166/wcc.2021.348
|View full text |Cite
|
Sign up to set email alerts
|

Temporal change of extreme precipitation intensity–duration–frequency relationships in Thailand

Abstract: Due to climate change, many research studies have derived the updated extreme precipitation intensity–duration–frequency relationship (IDF curve) from forecasted sub-hourly rainfall intensity time series, which is one of the most important tools for the planning and designing of hydraulic infrastructures. In this study, the IDF curves (1990–2016) of the six regions and procedures are used in accordance with those of the Royal Irrigation Department (RID)’s study (1950–1988). Each set of IDF relationships consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Utilizing the Long Ashton Research Station Weather Generator (LARS-WG), a stochastic weather generator, and the rainfall disaggregation tool Hyetos, they investigated a methodology based on the spatial downscaling-temporal disaggregation method (DDM) to develop future IDFs. Additionally, Yamoat et al (2022) developed IDF curves for six regions of Thailand, i.e., the Northern, Northeastern, Central, Western, Eastern, and Southern regions. They found that using accurate historical sub-hourly rainfall time series to create a set of IDF curves would be more reliable than using forecasted rainfall modeling.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing the Long Ashton Research Station Weather Generator (LARS-WG), a stochastic weather generator, and the rainfall disaggregation tool Hyetos, they investigated a methodology based on the spatial downscaling-temporal disaggregation method (DDM) to develop future IDFs. Additionally, Yamoat et al (2022) developed IDF curves for six regions of Thailand, i.e., the Northern, Northeastern, Central, Western, Eastern, and Southern regions. They found that using accurate historical sub-hourly rainfall time series to create a set of IDF curves would be more reliable than using forecasted rainfall modeling.…”
Section: Introductionmentioning
confidence: 99%
“…A chuva de projeto deve considerar a relação entre a intensidade, duração e frequência, denominada de relações IDF (MIRHOSSEINI et al, 2012;SUN et al, 2019). Alguns autores usam a relação altura ou profundidade no lugar da intensidade, denominando de relação DDF (YAMOAT et al, 2022). Essas relações podem ser expressas de forma gráfica, as chamadas curvas IDF, ou por meio de equações, denominadas de equações IDF (ou DDF).…”
Section: Introductionunclassified